Exploring selective learning in enhancing effective learning interest among grade 10 learners in schools in the Motheo district - Katlego Mabulana; Kananga Robert Mukuna (International Journal of Studies in Inclusive Education)
Teaching and learning in South Africa has been a concern. Schools have inflexible curriculum to accommodate learning interests of the learners. This causes numerous disadvantages to learners, such as dropping out, unstable teaching and learning environments, lack of readiness for higher education, and many more. The study explores how selective learning could enhance effective learning interest among grade 10 learners at schools in the Motheo district, Free State province, South Africa. Selective learning is the learner’s decision to select and learn relevant subjects within the curriculum framework, guided by one’s learning interest. This study adopted a qualitative approach and used a qualitative case study research design and interpretive paradigm. Semi-structured interviews with open-ended questions were used as a data collection instrument. Eight participants were purposively selected from two high schools. Participants were teachers from rural and urban-based schools with more than two years of teaching experience. Thematic analysis was used to analyse qualitative data. The results showed that selective learning could enhance effective learning interest by creating tolerable learning, enhancing cognitive skills, engaging teaching and learning, and creating academic excellence. Thus, this study concludes that selective learning can enhance effective learning interest among grade 10 learners in schools in the Motheo district of the Free State province.